Hyperpolarized Metabolic MR Imaging of Acute Myocardial Changes and Recovery after Ischemia-Reperfusion in a Small-Animal Model - O h-Ici, Darach; Wespi, Patrick; Busch, Julia; Wissmann, Lukas; Krajewski, Marcin; Weiss, Kilian; Sigfridsson, Andreas; Messroghli, Daniel; Kozerke, Sebastian (Radiology, 2016)
To implement hyperpolarized magnetic resonance (MR) imaging in an animal model of ischemia-reperfusion and to assess in vivo the regional changes in pyruvate metabolism within the 1st hour and at 1 week after a brief episode of coronary occlusion and reperfusion. All animal experiments were performed with adherence to the Swiss Animal Protection law and were approved by the regional veterinary office. A closed-chest rat model was implemented by using an inflatable balloon secured around the left coronary artery. Animals were placed in an MR system 5-7 days after surgery. [1-(13)C]pyruvate was polarized by using a home-built multisample hyperpolarizer. Hyperpolarized pyruvate was injected at five stages: at baseline; at reperfusion after 15 minutes of coronary occlusion; and at 30 minutes, 60 minutes, and 1 week after ischemia reperfusion. The conversion of pyruvate into lactate and bicarbonate was imaged by using dedicated MR sequences alongside wall motion and delayed enhancement imaging. After imaging, the heart was removed and stained to delineate the area at risk (AAR). Differences between AAR and remote myocardium were assessed by using a repeated measures analysis of variance and a post hoc Bonferroni multiple comparison test. Data were collected in 12 animals. Occlusion led to hypokinesia of the anterior or anterolateral segments of the myocardium. At reperfusion, the average lactate-to-bicarbonate ratio increased in the AAR relative to that at baseline (from 1.93 ± 0.48 to 3.01 ± 0.74, P < .001) and was significantly higher when compared with that in the remote area (1.91 ± 0.38, P < .001). In the 60 minutes after occlusion, the lactate-to-bicarbonate ratio in the AAR recovered but was still elevated relative to that in the remote area. One week after ischemia-reperfusion, no difference between AAR and remote area could be detected. Hyperpolarized metabolic MR imaging can be used to successfully detect acute changes in [1-(13)C]pyruvate metabolism after ischemia-reperfusion, thereby enabling in vivo monitoring of the metabolic effects of reperfusion strategies.